Tenth Anniversary of the Audiovisual Translation Study Programme: The Commemoration of a Decade of Work - Bagdžiūtė, Indrė; Jakaitytė, Gabrielė; Šedvydytė, Viktorija (Respectus Philologicus, 2023)
This review focuses on the celebration of the tenth anniversary of the Audiovisual Translation study programme that took place at Vilnius University Kaunas Faculty. TELL ME MORE: Translation Conference for Students and Early Career Researchers took place on April 25, 2023, and on the following day, April 26, 2023, the tenth anniversary of the Audiovisual Translation study programme was commemorated. In the article, the work carried out over the decade, the scientific publications and conferences organised, the changes in the study programme, the dynamics of the graduates, and the contribution of the social partners to the development and improvement of the Audiovisual Translation study programme were presented.